Artificial Intimacy and Islamic Jurisprudence: Legal and Ethical Perspectives on Sex Robots - Hammad, Hamza Abed Al-Karim (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
In light of the integration of artificial intelligence and the substantive progress in the robotics industry, a type of robots called sex robots has emerged, which some see as an alternative to natural sexual relations. A man finds a “female robot” as an alternative to a real woman and has a sexual relationship with the female robot, and the same applies to women. Therefore, this research aims to present the jurisprudential view on having sexual relations with robots. The research used the descriptive analytical method based on describing the nature of sex robots, then extrapolating the jurisprudential view of this sexual relationship from jurisprudential sources. As for the results and conclusions, the research concluded that the jurisprudential vision of this topic is represented in the prohibition of having sexual relations with robots in all their forms, and it is not permissible to use a robot for sexual purposes except when necessary; so that if a man or woman does not have to either use a robot or commit adultery, then use is permissible out of necessity; based on the opinion of the jurists of the Hanafi school, which sees masturbation as permissible in the event of fear of adultery, and the opinion of the jurists of the Hanbali school that masturbation is not permissible except when necessary, The scientific contribution of this study is evident as it deals with a realistic issue that has become widespread in contemporary times. This issue is not known to many researchers as well as the general public. Thus, it was necessary to present the jurisprudential perspective. Moreover, this study may be the first of its kind to address this topic.